PENGARUHMODEL PEMBELAJARAN SQ3R ( SURVEY, QUESTION, READ, RECITED, REVIEW) TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SEMESTER GENAP SMA NEGERI 1 KOTA AGUNG TANGGAMUS TAHUN PELAJARAN 2015/2016 - Fitria, Nur (LPPM STKIP PGRI Bandar Lampung, 2016)
To optimize the learning process of a teacher, must be able to choose the model, methods and learning strategies appropriate to the material to be delivered. By the selection of appropriate learning model can improve student learning outcomes and provide a positive influence on the effectiveness of the learning process. The purpose of this research was to determine whether there is influence of SQ3R models (Survey, Question, Read, recited, Review) on learning outcomes of economics students in the second semester at X grade of SMA 1 Kota agung Tanggamus academic year 2015/2016. In this study the authors used the experimental method. In analysing the data, the writer use t-test. Samples were taken using cluster random sampling technique. Instruments using in this study was multiple choice tests. Based on the calculation results of hypothesis testing that has been done with the author, it was obtained that t-cal = 4.73 and the distribution tables at the level of 5% was obtained t-tab = 2.00 and thus it is proved that t-cal > t-tab. It can be concluded that